Oocyte development, meiosis and aneuploidy - MacLennan, Marie (Academic Press, 2015)
Meiosis is one of the defining events in gametogenesis. Male and female germ cells both undergo one round of meiotic cell division during their development in order to reduce the ploidy of the gametes, and thereby maintain the ploidy of the species after fertilisation. However, there are some aspects of meiosis in the female germline, such as the prolonged arrest in dictyate, that appear to predispose oocytes to missegregate their chromosomes and transmit aneuploidies to the next generation. These maternally-derived aneuploidies are particularly problematic in humans where they are major contributors to miscarriage, age-related infertility, and the high incidence of Down's syndrome in human conceptions. This review will discuss how events that occur in foetal oocyte development and during the oocytes’ prolonged dictyate arrest can influence meiotic chromosome segregation and the incidence of aneuploidy in adult oocytes.